Control loop foundation : batch and continuous processes - Blevins, Terrence L. (International Society of Automation, 2011)
In this in-depth book, the authors address the concepts and terminology that are needed to work in the field of process control. The material is presented in a straightforward manner that is independent of the control system manufacturer. It is assumed that the reader may not have worked in a process plant environment and may be unfamiliar with the field devices and control systems. Much of the material on the practical aspects of control design and process applications is based on the authors personal experience gained in working with process control systems. Thus, the book is written to act as a guide for engineers, managers, technicians, and others that are new to process control or experienced control engineers who are unfamiliar with multi-loop control techniques. After the traditional single-loop and multi-loop techniques that are most often used in industry are covered, a brief introduction to advanced control techniques is provided. Whether the reader of this book is working as a process control engineer, working in a control group or working in an instrument department, the information will set the solid foundation needed to understand and work with existing control systems or to design new control applications.